2011
DOI: 10.1007/s12230-011-9213-4
|View full text |Cite
|
Sign up to set email alerts
|

Potato Seed Piece Size, Spacing, and Seeding Rate Effects on Yield, Quality and Economic Return

Abstract: It has been observed that potato producers often focus more on the quantity of potato seed pieces being planted per unit area than on seed piece size and placement within the row. This study compared the effects of seed quantity per unit area (Mg ha −1 ) or seed piece size and in-row spacing on potato yield and quality. Hand-cut certified seed of three potato cultivars (Alturas, Russet Norkotah, Ranger Russet) of three size classes (42, 64 or 85 g) were planted at in-row seed piece spacings of 20, 30 or 40 cm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Studying Atlantic and Monona under non-irrigated conditions in Ohio, seed-piece size between 35 and 58 g did not affect yield (Kleinhenz and Bennett 1992). Rykbost and Locke (1999) reported that three russet cultivars grown under irrigation yield highest when seedpiece weight was at least 50 g (Russet Norkotah) or 64 g (Russet Burbank and Century Russet); Bohl et al (2011) reported 64 g for Alturas, Ranger Russet and Russet Norkotah. These studies agreed with the findings here on Atlantic.…”
Section: Yieldmentioning
confidence: 98%
See 1 more Smart Citation
“…Studying Atlantic and Monona under non-irrigated conditions in Ohio, seed-piece size between 35 and 58 g did not affect yield (Kleinhenz and Bennett 1992). Rykbost and Locke (1999) reported that three russet cultivars grown under irrigation yield highest when seedpiece weight was at least 50 g (Russet Norkotah) or 64 g (Russet Burbank and Century Russet); Bohl et al (2011) reported 64 g for Alturas, Ranger Russet and Russet Norkotah. These studies agreed with the findings here on Atlantic.…”
Section: Yieldmentioning
confidence: 98%
“…Studies on Russet Burbank gave similar results (Iritani et al 1972;Schotzko et al 1984) concluding that optimal yields occurred when seed-piece weight was 57 g and seed spacing was 23 cm. Bohl et al (2011) observed that, across three russet cultivars, yield increased to seed-piece size of 64 g and spacing of 30 cm. They also reported that there was no difference in yield for the same amount of seed planted regardless of seedpiece size or spacing.…”
Section: Introductionmentioning
confidence: 96%
“…In the last year of the study, potato cultivars Valfi, Blaue St. Galler and HB Red (with purpleand red-colored flesh) were characterized by predominance (76-92%) of small tubers. According to Bohl et al (2011), growth regulators decrease the percentage of medium-sized potato tubers. Blauer et al (2013) demonstrated that the application of gibberellic acid (GA) decreased the percentage of tubers weighing 198 g and more and increased the share of smaller tubers in red-skinned potatoes of cv.…”
mentioning
confidence: 99%
“…For cvs. Alturas, Russet Norkotah, and Ranger Russet, 30 cm resulted in the highest yields (Bohl et al 2011). Arsenault et al (2001) studied eight cultivars and found that an in-row spacing of 25 cm proved the highest marketable yield seven out of eight varieties.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, producers choose row spacing and plant populations that minimize seed costs but maximize yields. For potato, Solanum tuberosum L., variety, seed piece size, tuber size, and chip or fresh markets all play a role in deciding which in-row spacing is used (Schotzko et al 1984;Creamer et al 1999;Bohl et al 2011). In general, as in-row spacing increases, so does tuber size.…”
Section: Introductionmentioning
confidence: 99%